1997
DOI: 10.1111/j.1600-0773.1997.tb00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tolbutamide on ATP‐Sensitive K+ Channels from Human Right Atrial Cardiac Myocytes

Abstract: Abstract:In order to gain further insight into possible deleterious effects on ischaemia-induced myocardial damage induced by sulfonylureas when administered to humans, the effects of tolbutamide on ATP-sensitive Kf ( K A T~) channels from human right atrial myocytes were studied. Single myocytes were enzymatically isolated from human right atrium. The cell-attached and inside-out configuration of the patch-clamp technique were employed at room temperature (both the pipette and the bath solution contained high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…5). The low tolbutamide sensitivity of Kir6.2/ SUR2A currents is consistent with that reported for native cardiac K ATP channels (K i~1 mmol/l; ref [85,143]) and is similar to that found when Kir6.2DC36 is expressed in the absence of a sulphonylurea receptor (K i~2 mmol/l) [81]. Thus it appears that SUR2A, unlike SUR1, does not confer high-affinity tolbutamide inhibition on the K ATP channel.…”
Section: Sulphonylurea Actionsupporting
confidence: 74%
See 1 more Smart Citation
“…5). The low tolbutamide sensitivity of Kir6.2/ SUR2A currents is consistent with that reported for native cardiac K ATP channels (K i~1 mmol/l; ref [85,143]) and is similar to that found when Kir6.2DC36 is expressed in the absence of a sulphonylurea receptor (K i~2 mmol/l) [81]. Thus it appears that SUR2A, unlike SUR1, does not confer high-affinity tolbutamide inhibition on the K ATP channel.…”
Section: Sulphonylurea Actionsupporting
confidence: 74%
“…The single-channel conductance of both cardiac and beta-cell K ATP channels in symmetrical 140 mmol/l K + solutions lies between 55±80pS, depending on the temperature at which the recordings are made [8,16,40,41,143]. In smooth muscle, the reported single-channel conductance varies widely, suggesting that there might be more than one type of K ATP channel in this tissue [42].…”
mentioning
confidence: 99%
“…30 Interestingly, human atrial cells are also reported to have high sensitivity to blockade by tolbutamide. 31 More direct evidence for a role of SUR1 subunits in forming cardiac K ATP channels was provided by the finding that antisense oligonucleotides against SUR1 inhibit K ATP channel currents in cultured neonatal rat ventricular cells. 12 In the present study, we were able to record K ATP channels from ventricular myocytes isolated from SUR1-null hearts that were blocked by cytosolic ATP in the micromolar range and with a unitary conductance similar to that previously reported for ventricular K ATP channels.…”
Section: Sur1 Expression In the Heartmentioning
confidence: 99%
“…K ATP channel composition in atrial myocytes is not yet established, but the single channel conductance, at room temperature, has been shown to range from 58 pS in rats (8) to 73 pS in humans (44). The lower value is close to the single channel conductance of KIR6.1/KIR6.2 heterotetramers coassembled with SUR2A (see Introduction).…”
Section: Perspectivesmentioning
confidence: 99%